2010
DOI: 10.1177/0272989x10377661
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Internet and Ratings of Information Sources for Medical Decisions: Results from the DECISIONS Survey

Abstract: Background. The rise in Internet use for seeking health information raises questions about the role the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 21 publications
5
89
0
4
Order By: Relevance
“…Additionally, a recent paper assessing participants' use of a web-based smoking cessation tool found that increased use of interactive website features and more frequent use of the website contributed to sustained smoking cessation [34]. Increased interactivity may play a key role in using the Internet to improve decision-making outcomes [20], such as expanding the use of a values clarification tool or expanding opportunities for patients to provide feedback throughout the website [44], such as brief quizzes about PCa facts.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent paper assessing participants' use of a web-based smoking cessation tool found that increased use of interactive website features and more frequent use of the website contributed to sustained smoking cessation [34]. Increased interactivity may play a key role in using the Internet to improve decision-making outcomes [20], such as expanding the use of a values clarification tool or expanding opportunities for patients to provide feedback throughout the website [44], such as brief quizzes about PCa facts.…”
Section: Original Researchmentioning
confidence: 99%
“…In general, online health information seekers say they feel more confident in starting a discussion with their doctor than those who do not use the Internet to find health information [19]. Delivering accurate and current medical information is important for open communication between patients and doctors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Searching the internet for a significant other's health condition is also common (Fox, 2011). When people face a health decision, the internet is their second most influential source of information after clinician advice (Couper et al, 2010). In a survey of over 8000 Americans, those with a chronic health condition were more likely to search the internet for health information (Bundorf et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is a central problem given the prevalence of internet health information searches (Fox, 2011) and the importance people put on the information they access (Couper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, 77% of adults report using the Internet (Pew Internet & American Life Project, 2011a), with more than 80% of these (61% of all adults) seeking health information via the Internet (Rainie, 2011). A recent study found that, among Internet users, the Internet was second only to health care providers as an information source important in their health decisions (Couper et al, 2010). Earlier research had shown that the Internet may empower patients to improve their health behaviors and to take a more active role in their health care (Horrigan, Rainie, & Fox, 2001).…”
mentioning
confidence: 99%